2020
DOI: 10.1186/s12917-020-02487-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on eggshell apex abnormality (EAA) syndrome in France: isolation of Mycoplasma synoviae is frequently associated with Mycoplasma pullorum

Abstract: Background: Mycoplasma synoviae (MS) is known to cause Eggshell Apex Abnormality (EAA) syndrome characterized by an altered shell surface with increased translucency on the apex. However, no large-scale studies have been conducted to obtain prevalence data of EAA and MS isolates associated to this syndrome. This manuscript reports the results of two field studies performed in the French poultry industry (2015-2017): focusing mainly on investigation of presence and prevalence of EAA in different types of laying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…From various species over 10 years and antibiotic resistance [83] Mycoplasmas MALDI for screening of poultry flocks [84]…”
Section: Staphylococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…From various species over 10 years and antibiotic resistance [83] Mycoplasmas MALDI for screening of poultry flocks [84]…”
Section: Staphylococcusmentioning
confidence: 99%
“…In the work of Cisneros-Tamayo et al [84], MALDI-TOF was used to screen poultry flocks for Mycoplasma and it was found that Mycoplasma synoviae was detected in 25/28 flocks tested while Mycoplasma pullorum was observed in 56% of flocks considered. In addition to providing data on prevalence, the paper demonstrates the use of MALDI-TOF technology for rapid screening of poultry flocks for Mycoplasma infection.…”
Section: Streptococcus Salivarius Streptococcus Equinus Andmentioning
confidence: 99%
“…Mycoplasma synoviae ( M. synoviae ) is one of the most important poultry pathogens, leading significant economic losses to the poultry industry worldwide. M. synoviae infection can cause infectious synovitis, airsacculitis, a high incidence of shell breakage, and egg production loss ( Kleven et al, 1975 ; Cisneros-Tamayo et al, 2020 ). Substantial variations in pathogenicity and tissue tropism are observed among M. synoviae isolates, and some strains cause no infection whereas others cause respiratory disease or synovitis ( Lockaby et al, 1998 ; Lockaby and Hoerr, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasma synoviae ( MS ) has been described as a major pathogen involved in synovitis, airsacculitis, eggshell apex abnormality, and egg drops ( 1 , 2 ). MS cooperates with other pathogens, such as infectious bronchitis virus (IBV) and Newcastle disease virus (NDV), and tends to exacerbate pathogenesis in chickens ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%